Religious Education among Minority Muslim Schools in Israel: The Condition and Overview - Nohad 'Ali (Jurnal Pendidikan Islam, 2017)
The education system in Israel is a centralized system including both Jews and Arabs. Therefore, these schools are controlled both administratively (including funding) and curricular by the government. From the data obtained in the field, there is an unbalanced comparison between Jewish and non-Jewish educational systems (including Arabic) in Israel. This shows the lack of resource justice, budgetary discrimination, and less developed learning and development programs, especially seen in the Arabic education system. The main purpose of education in Israel is to help the Jewish majority group and intend to maintain Jewish domination. Arabic education applied in Israel has been the subject of Muslim and Arab intellectual criticism. Their rejection is mainly related to the inequality, discrimination and marginalization facing Arab education. With this perspective, the Islamic movement has spurred Islamic educational institutions to uphold and maintain the religious identity and national identity of Muslim minority members in Israel. The article describes the education system in Israel including the religious education system as well as the education system for minorities in Israel.